Renal cancer. Issue 10 (October 2022) - Janebdar, Husay; Fernandes, Megan; Manson-Bahr, David
Abstract: Renal cell carcinoma (RCC) is an adenocarcinoma of the renal cortex. It is the commonest type of kidney cancer and accounts for over 85% of renal cancer diagnoses. The remaining malignancies are transitional cell carcinomas, sarcomas, Wilms' tumour, and rarely lymphomas and metastatic deposits. 10%–15% of renal masses are benign, such as oncocytomas and angiomyolipomas. Simple renal cysts are benign, however more complex renal cysts have a risk of being malignant. Renal cell carcinoma is commonly diagnosed at an earlier stage due to the widespread availability of imaging, and as a result the described classic triad of symptoms of haematuria, renal angle pain and a palpable mass is increasingly uncommon. The management of renal cancer includes active surveillance for older, comorbid patients, nephron-sparing surgery or ablative therapies for smaller renal masses, radical nephrectomy for larger tumours, and systemic treatment with a combination of immunotherapies and tyrosine kinase inhibitors and for metastatic disease.